Performance evaluation of large contracting companies - Ngan, See Pyng. (2009)
The main objective of this dissertation is to investigate the methods, management tools and techniques used by large, local construction companies to evaluate the performance of the company. The aim of this research work is to bring about a comprehensive management model for performance evaluation of large, local construction companies and apply such a model to a large, local construction company, CASESTUDY company.